A case series of urogenital fistulas - Selukar, Dhananjay; Pothare, Amit Narayan; Meshram, Kunal; Jibhkate, Nikhilesh; Rahangdale, Vinay; Perka, Shrikant (International Surgery Journal, 2017)
Background: Urogenital fistula is an abnormal fistulous communication that occurs between the bladder and cervix or uterus; between the ureter and vagina, uterus, or cervix; and between the urethra and vagina. Most cases in developing countries are of obstetric etiology, resulting from prolonged neglected obstructed labour, and around 1–2 per 1000 deliveries may be affected. The majority of UGFs in developed countries are a consequence of gynecological surgery, mainly hysterectomies. Present study focuses on the various presentations and the different modalities of surgeries done for cases of urogenital fistulas at our institute. Methods: A total 19 cases of urogenital fistula were studied in detail as per proforma. Two patients were operated on emergency basis because of early presentation in postoperative period. For others a pre-operative waiting period of 3-6 months was followed after development of fistula. During this period initially bilateral DJ stenting was tried in all patients, in hope of spontaneous closure of fistulas. Two patients whose fistulas closed spontaneously are not subjected to surgery. Rest all cases were managed surgically by standard surgical procedures. Results: Study was conducted between, February 2015 to February 2017. A total 19 patients studied. In 2 patients, fistula healed spontaneously while in 17 patients, surgery was needed. Most common age group affected is 2nd decade of life about 47.36%. In our study gynecological surgeries predominate with 57.89% followed by obstetric cases in 26.31%. Most of patients presented with continues dribbling of urine through vagina with normal voiding pattern in about 78.94% of cases. Overall transabdominal procedures had nearly 100% success rate, mainly because of better dissection, visualization and use of vascularized graft which prevents recurrence. 1 recurrence was seen in transvesical extraperitoneal approach because of undiagnosed another fistulous tract. Ureteric reimplantation was 100% successful in ureterogenital fistulas. Vaginal approach with use of Mortius flap had 75% success rate with 1 recurrence because of flap necrosis. Mean duration of surgery was 120 minutes and mean hospital stay was 8 days.. Conclusions: Urogenital fistulas are the most distressing complications of obstetric and gynecological surgeries. Obstetric causes predominate in developing countries while gynecological surgeries predominate in developed countries. Despite the good results of surgical repair, attempt should be focused on the prevention of VVF.